Modulating the bistable potential energy separatrix for augmented broadband vibration energy harvesting. (February 2017) - Ouellette, Scott A; Todd, Michael D
In recent years, increased interest in broadband vibration energy harvesting schemes has been a main topic of interest among researchers. One of the most successful approaches toward broadband vibration energy capture has been with bistable inertial generators. These devices leverage a nonlinear restoring force to exploit the hardening spring response to increase the resonant frequency bandwidth beyond the characteristically narrowband resonant frequency associated with conventional linear inertial generators. However, one issue with bistable energy harvesters is the presence of low-amplitude oscillations whose energy is insufficient to overcome the potential energy separatrix barrier between the competing potential wells. This article presents the effects of controlling the magnitude of the potential energy separatrix by means of a high-permeability electromagnet in order to increase the resonant response bandwidth for low-amplitude harmonic excitations. An analytical model of the bifurcation space resulting from two control parameters is presented along with an experimental validation study. Finally, an open-loop control law is developed and tested to validate the resonant frequency bandwidth augmentation for harmonic chirp excitations.